A latent profile analysis of PTSD symptoms among UK treatment seeking veterans. Issue 1 (31st December 2019) - Murphy, D.; Ross, J.; Busuttil, W.; Greenberg, N.; Armour, C.
ABSTRACT: Background : Significant numbers of individuals leave the military and experience symptoms of posttraumatic stress disorder (PTSD). Veterans with PTSD symptoms rarely experience them in isolation, more commonly they are co-morbid with a range of other difficulties. Objective : Latent profile analysis (LPA) was used to explore the heterogeneity of PTSD symptom presentation. Following this, regression analysis was used to examine variables that predicted membership to the identified PTSD profiles. Methods : Data on childhood adversity, socio-demographic characteristics and mental health outcomes was collected from 386 male veterans who had engaged with mental health services in the UK. Results : LPA identified a six-profile model to best describe the sample. There was a Low symptom profile, a Severe symptom profile and four Moderate symptom profiles. The Severe symptom profile was the largest one, accounting for 37.57% of the sample. Five out of the six profiles had mean PTSD scores above the cut-off for probable PTSD. Higher rates of common mental health difficulties were associated with more symptomatic profiles. Discussion : As the vast majority of veterans met criteria for probable PTSD, the finding of six different profiles differing primarily quantitatively, but to some extent also qualitatively, suggests the importance of moving away from a 'one-size fits all' approach when it comes to treatments, towards developing interventions that are tailored to meet the specific PTSD and co-morbid symptoms profiles. HIGHLIGHTS: Six PTSD profiles were identified in UK treatment-seeking military veterans. The differences between the profiles were primarily quantitative. Qualitative differences between profiles emerged in relation to the PTSD avoidance symptoms. Common mental health difficulties were consistently associated with more symptomatic profiles.